Three-dimensional synchrotron virtual paleohistology: A new insight into the world of fossil bone microstructures - Sanchez, S.; Ahlberg, P.; Trinajstic, Katherine; Mirone, A.; Tafforeau, P. (Microscopy Society of America, 2012)
The recent developments of phase-contrast synchrotron imaging techniques have been of great interest for paleontologists, providing three-dimensional (3D) tomographic images of anatomical structures, thereby leading to new paleobiological insights and the discovery of new species. However, until now, it has not been used on features smaller than 5–7 mm voxel size in fossil bones. Because much information is contained within the 3D histological architecture of bone, including an ontogenetic record, crucial for understanding the paleobiology of fossil species, the application of phase-contrast synchrotron tomography to bone at higher resolutions is potentially of great interest. Here we use this technique to provide new 3D insights into the submicron-scale histology of fossil and recent bones, based on the development of new pink-beam configurations, data acquisition strategies, and improved processing tools. Not only do the scans reveal by nondestructive means all of the major features of the histology at a resolution comparable to that of optical microscopy, they provide 3D information that cannot be obtained by any other method.